Role of Lamivudine as Preemptive Therapy in Cancer Patients with Hepatitis B undergoing Chemotherapy - Andree Kurniawan; Andri Sanityoso Sulaiman (The Indonesian Society for Digestive Endoscopy, 2013)
Patients diagnosed with hematology malignancy and solid tumor who underwent chemotherapy, frequently encountered hepatitis B reactivation. Patients with blood cancer, including lymphoma, had higher risk of reactivation compared to those with solid tumor. Steroid and immunosuppressant drugs contained in chemotherapy regimens were responsible for those events. Hepatitis B reactivation during chemotherapy treatment could contribute to acute liver failure and increase mortality. Administration of analog nucleoside therapy in this group of patient prior to the initiation of chemotherapy could prevent reactivation of hepatitis B.A 43 year-old male patient were diagnosed with diffuse large B cell non-Hodgkin lymphoma stadium II BE (oropharynx) under chemotherapy and had hepatitis B. In this evidence based case report, we reported a critical appraisal of the role of lamivudine as preemptive therapy in blood cancer and solid tumor.Keywords: chemotherapy, hepatitis B reactivation, malignancy